18F-Choline PET/CT and Prostate MRI for Staging Patients With Biochemical Relapse After Irradiation for Prostate Cancer. (November 2015) - Quero, Laurent; Vercellino, Laetitia; de Kerviler, Eric; Mongiat-Artus, Pierre; Culine, Stephane; Merlet, Pascal; Ravery, Vincent; Meria, Paul; Desgrandchamps, Francois; Hennequin, Christophe
<x xml:space="preserve">Abstract</x> Purpose The aim of this study was to assess the value of combining MRI and 18F-fluorocholine (FCH) PET/CT for patients with a biochemical relapse (BR) after prostate radiotherapy or brachytherapy. Patients and Methods All patients with a BR (BR definition: nadir prostate-specific antigen, +2 ng/mL) had a multiparametric MRI and FCH PET/CT if there was no clinical sign of relapse. Identification of the relapse was considered positive if both imaging techniques were concordant or in case of pathological relapse confirmation. Results Sixty-five consecutive patients were analyzed. Initial treatment was external beam radiation therapy (EBRT; n = 40), surgery followed by EBRT (n = 11), or brachytherapy (n = 14). Gleason score was 6 in 23 patients, 7 in 35 patients, and 8 to 10 in 7 patients. Median prostate-specific antigen value at the time of relapse was 7.6 ng/mL. Determination of relapse location was identified in 46 patients (70.7%). Relapses were only local in 24 patients (37%), nodal in 16 (24.6%), and distant in 9 (14%). In 4 cases, MRI showed a local relapse not seen by FCH PET/CT. Among the 24 patients with an isolated local relapse, 13 underwent a confirmatory biopsy and 9 were positive. At the end, only 7 patients (11%) could have a salvage local treatment: cryotherapy of the prostate in 6 cases and 1 nodal EBRT. Conclusions In case of BR after radiotherapy or brachytherapy, combining MRI and FCH PET/CT could identify the site of relapse in 70% of patients. This could facilitate the selection of the patients for local salvage treatment.